Bridging technologies in the regional knowledge space: Measurement and evolution - Stefano Basilico; Holger Graf (Friedrich Schiller University Jena, 2020)
The concept of Bridging Technologies (BTs) refers to technologies which are important for the regional knowledge base by connecting different fields and thereby enabling technological development. We provide analytical tools to identify BTs and study their evolution over time. We apply these tools on several levels. Our findings indicate that large patenting regions are not necessarily the ones that embed most new technologies in their Knowledge Space (KS). Our findings reveal that the German KS became less dependent on important technologies, such as transport, machinery and chemicals over the period 1995-2015. Changes in the German KS in terms of the development of new BTs are due to a regionally dispersed process rather than driven by single regions.
Keywords: O33; O34; R11; 330; Knowledge Spaces; Network Analysis; Bridging Technology; Revealed Relatedness; GPT; Centrality